PENGARUH PENGALAMAN MEMBELI, KEMUDAHAN PENGGUNAAN DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG KONSUMEN PADA E-COMMERCE LAZADA (Studi Kasus Pada Konsumen Di Kecamatan Gianyar) - Dwijayanthi, Anak Agung Istri Agung Ovy; Meryawan, I Wayan; Rusmayanthi, Kadek intan; Nurakmalia, Ade (Universitas Ngurah Rai, 2024)
The rapid development of e-commerce has influenced consumer behavior, including in Gianyar District. However, there is limited research examining the factors that drive repurchase intention in e-commerce platforms like Lazada. This study aims to analyze the simultaneous and partial effects of purchasing experience, ease of use, and trust on repurchase intention in Lazada e-commerce within Gianyar District. The research utilizes purposive random sampling, involving 96 respondents as samples. The data sources include primary and secondary data, with the nature of the data being quantitative and qualitative. Data collection techniques employed include observation, interviews, questionnaires, and documentation studies. Data analysis was conducted using multiple linear regression. The findings reveal that purchasing experience, ease of use, and trust significantly and positively affect repurchase intention, both simultaneously and partially. These results underline the importance of these factors in enhancing consumer loyalty in e-commerce platforms.